Synthesis, magnetic and optical properties of core/shell Co1-x Zn x Fe2O4/SiO2 nanoparticles - Wahsh Mohamed (Nanoscale Research Letters, 2011)
Abstract The optical properties of multi-functionalized cobalt ferrite (CoFe2O4), cobalt zinc ferrite (Co0.5Zn0.5Fe2O4), and zinc ferrite (ZnFe2O4) nanoparticles have been enhanced by coating them with silica shell using a modified Stöber method. The ferrites nanoparticles were prepared by a modified citrate gel technique. These core/shell ferrites nanoparticles have been fired at temperatures: 400°C, 600°C and 800°C, respectively, for 2 h. The composition, phase, and morphology of the prepared core/shell ferrites nanoparticles were determined by X-ray diffraction and transmission electron microscopy, respectively. The diffuse reflectance and magnetic properties of the core/shell ferrites nanoparticles at room temperature were investigated using UV/VIS double-beam spectrophotometer and vibrating sample magnetometer, respectively. It was found that, by increasing the firing temperature from 400°C to 800°C, the average crystallite size of the core/shell ferrites nanoparticles increases. The cobalt ferrite nanoparticles fired at temperature 800°C; show the highest saturation magnetization while the zinc ferrite nanoparticles coated with silica shell shows the highest diffuse reflectance. On the other hand, core/shell zinc ferrite/silica nanoparticles fired at 400°C show a ferromagnetic behavior and high diffuse reflectance when compared with all the uncoated or coated ferrites nanoparticles. These characteristics of core/shell zinc ferrite/silica nanostructures make them promising candidates for magneto-optical nanodevice applications.